Penile cancer treatment costs in England. (December 2015) - Keeping, Sam; Tempest, Michael; Stephens, Stephanie; Carroll, Stuart; Sangar, Vijay
Abstract Background Penile cancer is a rare malignancy in Western countries, with an incidence rate of around 1 per 100, 000. Due to its rarity, most treatment recommendations are based on small trials and case series reports. Furthermore, data on the resource implications are scarce. The objective of this study was to estimate the annual economic burden of treating penile cancer in England between 2006 and 2011 and the cost of treating a single case based on a modified version of the European Association of Urology penile cancer treatment guidelines. Methods A retrospective (non-comparative) case series was performed using data extracted from Hospital Episode Statistics. Patient admission data for invasive penile cancer or carcinoma in situ of the penis was extracted by ICD-10 code and matched to data from the 2010/11 National Tariff to calculate the mean number of patients and associated annual cost. A mathematical model was simultaneously developed to estimate mean treatment costs per patient based on interventions and their associated outcomes, advised under a modified version of the European Association of Urologists Treatment Guidelines. Results Approximately 640 patients per year received some form of inpatient care between 2006 and 2011, amounting to an average of 1, 292 spells of care; with an average of 48 patients being treated in an outpatient setting. Mean annual costs per invasive penile cancer inpatient and outpatient were £3, 737 and £1, 051 respectively, with total mean annual costs amounting to £2, 442, 020 (excluding high cost drugs). The mean cost per case, including follow-up, was estimated to be £7, 421 to £8, 063. Results were sensitive to the setting in which care was delivered. Conclusions The treatment of penile cancer consumes similar levels of resource to other urological cancers. This should be factored in to decisions concerning new treatment modalities as well as choices around resource allocation in specialist treatment centres and the value of preventative measures.